Understanding the underlying mechanisms of Quiet Eye: the role of microsaccades, small saccades and pupil-size before final movement initiation in a soccer penalty kick - Piras, A.; Timmis, M.; Trofè, A.; Raffi, M. (European Journal of Sport Science, 2021)
Experts keep a steady final fixation at a specific location just before final movement initiation, the so-called "quiet eye" (QE). However, the eyes are rarely "quiet", and small eye movements occur during visual fixation. The current research investigated the subtle eye movements and underlying mechanisms immediately prior to and during QE. The gaze behaviour of 8 intermediate-level goalkeepers was recorded as they moved (either left or right) in an attempt to predict the future direction of the ball during a soccer penalty kick. Goalkeepers were more likely to predict the direction of the penalty, which was coupled with delaying movement initiation. The temporal sequence of microsaccade rates dropped ~1000 ms before goalkeepers` final movement initiation. Saccade rates increased, reaching a peak ~500 ms before final movement initiation, concomitant with microsaccades reduction. Microsaccades predicted the goalkeepers` direction, oriented to the right when goalkeepers moved to the right, and conversely to the left when they moved to the left. Microsaccades may be modulated by attention and appear functionally related to saccadic intrusions. Pupil-size increased proportionally with the lead up to the instance of the penalty being kicked, reaching a plateau at final movement initiation. In conclusion, microsaccades and small saccades could improve the perception of the soccer penalty kick, helping athletes during the period that precedes the critical movement initiation, shifting from covert to overt attention for identifying the useful cues necessary to guide the action.